Japan : 2009 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2009 Article IV Consultation highlights that although Japan was not at the center of the initial crisis, the collapse in external demand and financial spillovers have plunged the economy into a severe recession. Financial policies are focusing on strengthening the resilience of the financial system. Executive Directors have welcomed the support being provided by fiscal stimulus packages. On the monetary front, Directors have commended the authorities for their wide-ranging actions, which have helped to stabilize financial markets and facilitate corporate financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet